MODERN ORGANIZATIONAL ASPECTS OF THE TRANSFORMATION OF EDUCATIONAL ACTIVITIES: Array - Mingming, Wen; Chang, Liu; Prunenko, D.; Mamonov, K.; Troian, V. (Municipal economy of cities. Series: «Economy science», 2021)
It is established that in modern conditions there is an increase in the importance of human capital to address issues in the economy. In recent years, a new paradigm of development has been formed, which provides for the creation of a systemic environment of intellectual and innovative economy. In such conditions there is a need to rethink approaches to the implementation of the educational process, the formation of organizational structures. The aim of the work is to determine the modern organizational aspects of the transformation of educational activities, taking into account the changes taking place in Ukraine. To achieve this goal, the following tasks were solved: to characterize the transformation of the organizational structure of educational activities; identify areas for transformation of the organizational structure of educational activities. To ensure educational activities is important to form an effective organizational structure. In this context, it should be noted the directions of its transformation in terms of creating institutions in the structure of universities. In particular, considering the training of specialists in construction and civil engineering, it is noted that the main purpose of the Institute of Civil and Civil Engineering within the University is the formation and development of scientific and educational capacity in construction and engineering based on modern tools used in the market. construction, civil engineering, ecology, land administration and geographic information systems and technologies, the market of educational services. The necessity of application of modern information technologies for maintenance of educational activity is defined.